Zinc Supplementation Reduces Recurrent Acute Lower Respiratory Infection (ALRI) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Pneumonia is a frequent and serious human illness. In Bangladesh, Acute Lower Respiratory Infection (ALRI) is a major cause of death among young children. Childhood mortality can be reduced by 50% with detection and early treatment of illness with antibiotics and immunization. Zinc plays an important role in the optimal function of the immune system by reducing the risk, severity and duration of infectious diseases. Zinc supplementation improves health and cell mediated immunity. Objectives: This study is aimed at documenting effect of zinc supplementation in preschool children on reducing ALRI. Methods: This was a double blind random control trial interventional study among180 child, conducted at Comilla CMH, from January 2010 to December 2011. The children aged 6-60 months were selected randomly for comparison of effect of Zinc and Vitamin B-Complex on ALRI. Results: In the study population, male to female ratio was 1.05:1. Baseline average age was 32 months and weight for height was 92% Of NCHS mean. It was found that 89% children completed immunization as per EPI schedule, the rest 11% were partially immunized. Twenty nine percent children had family history of Atopy. This study showed 15 episodes of ALRI in Zinc group in the control B-Complex group (1.09episodes/child/year) during the six months follow-up. There was no association of ALRI with sex. The male female ratio in this respect was 1.07:1. In this study there was statistically significant and clinically important (67%) reduction of episodes of ALRI in oral Zinc supplement group. Conclusion: This finding strongly suggests that oral supplement of Zinc reduces episodes of ALRI in children. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18736 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 84-89